Pre-service Early Childhood Education Teachers’ Perception on Their Future Profession - Zeynep Temiz (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This study aims to explore pre-service ECE teachers’ perceptions of being a teacher in qualitative perspective. Particularly, pre-service ECE teachers’ descriptions of their motivation in choosing this profession, their satisfaction on their profession, and their career commitment to pursuit as a teacherand finally how their attitudes changes toward ECE throughout school years were investigated. A total of 20 female pre-service early childhood education teachers who were studying at the pre-school education program in in the Faculty of Education at METU participated in the study. Five pre-service ECE teachers from each 2nd, 4th, 6th, and 8th semesters participated voluntarily. Semi-structured interview was conducted with pre-service teachers. All of the interviews were audio recorded then transcribed. Qualitative analysis was utilized for data analysis. Findings revealed that majority of pre-service teachers recognized that their personality best fit into teaching profession as the love of children was a part of their personality. Yet, becoming an early childhood teacher was not a career dream for the other participants as they decided to become a teacher based on their score on University Entrance Exam. Prospective teachers who choose this profession willingly are satisfied with natural outcome of teaching profession. For instance, being called as “the teacher” by children is enough to make them satisfied with their occupation. Participants believed that studying early childhood education will provide wide range of career opportunities when they graduated.